A Case of Mollarets Meningitis In Apollo Hospitals Dhaka (Pulse, 2018)
Mollarets Meningitis is defined as a benign recurrent aseptic meningitis characterized by more than three episodes of fever, headache, meningeal irritation lasting typically 3-5 days. It has spontaneous recovery without any residual neurological deficit. Mollaret in 1944 described this extremely rare form of self-limiting aseptic recurrent benign meningitis. Here we present the report of a patient with Mollarets Meningitis with some atypical features. Early diagnosis may prevent prolonged hospital admissions, unnecessary investigations, and exposure to unnecessary medications, with their associated considerable costs.Pulse Vol.10 January-December 2017 p.42-46